2021
DOI: 10.5964/jspp.7297
|View full text |Cite
|
Sign up to set email alerts
|

The psychological and socio-political consequences of infectious diseases: Authoritarianism, governance, and nonzoonotic (human-to-human) infection transmission

Abstract: What are the socio-political consequences of infectious diseases? Humans have evolved to avoid disease and infection, resulting in a set of psychological mechanisms that promote disease-avoidance, referred to as the behavioral immune system (BIS). One manifestation of the BIS is the cautious avoidance of unfamiliar, foreign, or potentially contaminating stimuli. Specifically, when disease infection risk is salient or prevalent, authoritarian attitudes can emerge that seek to avoid and reject foreign outgroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 109 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…The effect of COVID-19 threat was robust to adjustment on several potential confounds including prior electoral success of conservative parties. Replicating recent results from Zmigrod et al (2021) and Karwowski et al (2020), we confirmed that pathogen threat effects can translate into real-world political outcomes, extending well-known effects of historical pathogen threats on ideological preferences to ongoing pandemics. With a 1% increase in pathogen threat salience is associated with between .08 to .41% supplementary votes for conservative parties.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The effect of COVID-19 threat was robust to adjustment on several potential confounds including prior electoral success of conservative parties. Replicating recent results from Zmigrod et al (2021) and Karwowski et al (2020), we confirmed that pathogen threat effects can translate into real-world political outcomes, extending well-known effects of historical pathogen threats on ideological preferences to ongoing pandemics. With a 1% increase in pathogen threat salience is associated with between .08 to .41% supplementary votes for conservative parties.…”
Section: Discussionsupporting
confidence: 79%
“…For example, evidence suggests that the 2014 Ebola outbreak did influence electoral preference for conservative candidates during federal elections held later that year (Beall et al, 2016; see Schaller et al, 2017 for a replication). Likewise, historical prevalence of nonzoonotic diseases predicted conservative votes for the 2016 US presidential election (Zmigrod et al, 2021), and research suggests that ideology differently relates to threat sensitivity, with liberals being more sensitive to economic threats and conservatives to pathogen related ones (Fiagbenu et al, 2021) .…”
mentioning
confidence: 99%
“…But an analysis of infectious diseases (split into STD and non-STD infections) and outcomes predicted by PST showed that the effects of pathogenic stress across the states of the USA can be almost exclusively explained by STDs (Hackman & Hruschka, 2013). It has been already found that human-to-human and multi-host transmissible infections (non-zoonotic diseases) account for PST findings and not zoonotic diseases that are only transmitted from animals to humans (O'Shea et al, 2022;Thornhill et al, 2010;Zmigrod et al, 2021). But what type of non-zoonotic infectious disease (e.g., bacterial, viral) and what exact disease (e.g., HIV, tuberculosis) contribute more to the cross-population differences can be explored more thoroughly in future studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…The parasite-stress theory of sociality proposes that in-group assortative sociality ( Thornhill & Fincher, 2014c ), which is “ preferential association among similar individuals who compose an in-group versus out-group or dissimilar others ” ( Fincher & Thornhill, 2012 ), is valued in areas of high parasite-stress ( Thornhill & Fincher, 2014a ). Empirical research supports the parasite-stress theory of sociality by showing that people in ecological settings of high pathogen risks are inclined to show strong in-group favoritism and out-group dislike ( Fincher and Thornhill, 2012 , Fincher et al, 2008 , Murray and Schaller, 2010 , O'Shea et al, 2022 , Santos et al, 2017 , Thornhill and Fincher, 2014a , Thornhill et al, 2010 , Tybur et al, 2016 , Zmigrod et al, 2021 ). As an anti-pathogen strategy ( Fincher and Thornhill, 2012 , Fincher et al, 2008 ), in-group assortative sociality is related to the behavioral immune system (BIS) ( Thornhill & Fincher, 2014b ), which is a set of cognitive, affective, and behavioral mechanisms for reducing disease threat ( Schaller, 2011 ).…”
Section: Introductionmentioning
confidence: 94%